Chromatic dispersion power penalties in orthogonal subcarrier--optical tandem single sideband systems - Abdul Rashid, Hairul Azhar; Chuah, Hean Teik; Tayahi, Moncef B.; Al-Qdah, Malik T.; Lee, Ruen Chung (2005)
This paper deals with power penalties in Optical Tandem Single Sideband system using orthogonal subcarriers due to chromatic dispersion. The upper and lower sideband orthogonality is affected by chromatic dispersion. This phase imbalance causes degradation of quadrature demodulation performance. The effect is demonstrated by a mathematical model and verified by simulation results.